2018
DOI: 10.3329/uhj.v13i2.37657
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Distal Transradial in the Anatomical Snuffbox versus Conventional Transradial Access for Coronary Angiography and Intervention-An Experience in 100 cases

Abstract: Background: Distal transradial access in the anatomical snuffbox has advantages over standard proximal access in terms of patient and operator comfort levels and risk of ischemia. Radial artery preservation could be a relevant issue in patients requiring multiple radial artery procedures and coronary bypass with the use of a radial graft or construction of Arterio-Venous fistula in patient of chronic kidney disease. One relevant drawback is the challenging puncture of a small and weak artery, with a steeper le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 11 publications
0
33
0
Order By: Relevance
“…Many operators suggest the benefits of this access over the standard radial access including easier left-sided access for aorto-coronary grafts, future proximal radial artery preservation, shorter time hemostasis and patient and operator comfort. However, few studies had compared the two approach and the published results remain controversial and limited [6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Many operators suggest the benefits of this access over the standard radial access including easier left-sided access for aorto-coronary grafts, future proximal radial artery preservation, shorter time hemostasis and patient and operator comfort. However, few studies had compared the two approach and the published results remain controversial and limited [6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…But the difference in left and right hands was not significantly. In some studies, the patient’s satisfaction was semi-quantized evaluated by using visual analog scale (VAS) [ 22 , 56 ]. The VAS score of pain was lower in dTRA group in comparison to TRA group [ 56 ].…”
Section: Complicationsmentioning
confidence: 99%
“…In some studies, the patient’s satisfaction was semi-quantized evaluated by using visual analog scale (VAS) [ 22 , 56 ]. The VAS score of pain was lower in dTRA group in comparison to TRA group [ 56 ]. Al-Azizi KM et al [ 28 ] reported that the novel approach could increase the satisfaction not only in patients, but also in operators and nurses.…”
Section: Complicationsmentioning
confidence: 99%
“…Thus, the patients are comfortable and the procedure is well tolerated [26]. Amin et al [27] used the VAS to evaluate the degree of pain during haemostasis and found that the pain scores in the d-TRA group were significantly lower than those in the c-TRA group. AI-Azizi et al [28] found that d-TRA not only d-TRA has very few complications, such as haematoma, haemorrhage, pseudoaneurysm and arteriovenous fistula [24,28], which may be related to the AS with a bony basement surrounded by tendons.…”
Section: Discussionmentioning
confidence: 99%